Characterization With Scanning Electron Microscopy/Energy-Dispersive X-ray Spectrometry of Microtraces From the Ligature Mean in Hanging Mechanical Asphyxia: A Series of Forensic Cases. (March 2018) - Maghin, Francesca; Andreola, Salvatore Ambrogio; Boracchi, Michele; Gentile, Guendalina; Maciocco, Francesca; Zoja, Riccardo
Abstract : Abstract: The authors applied scanning electron microscopy with energy-dispersive x-ray spectrometry to the furrow derived from hanging means. The study was conducted with the purpose to detect possible extraneous microtraces, deriving from the ligature, that could have had an interaction with the cutaneous biological matrix, thanks to a transfert mechanism, in the proximities of the lesion. Fifteen cutaneous samples of the furrow and an equal number of fragments of graphite tape, directly positioned on the lesion produced by the ligature mean and used as a "conductor" of possible traces, were analyzed using scanning electron microscopy with energy-dispersive x-ray spectrometry. The research of microscopic traces on the furrow using this technique highlights extraneous traces leading to 3 main categories: natural fabrics, and synthetic and metallic materials, excluding possible environmental pollutants. The analysis, run on 7 hanging deaths, made available by the judicial authority, found a morphological and compositional compatibility with the traces found on the cutaneous furrow produced during hanging. The technique used in this study is innovative in the pathological-forensic field, and can be considered useful in clarifying and studying this typology of asphyxia leading to a specific ligature material, when missing, or attributing the cause of death to hanging when the furrow is not macroscopically obvious.